Business cycle drivers in Nigeria: Some insights from an estimated DSGE model - Babatunde S. Omotosho (West African Journal of Monetary and Economic Integration, 2019)
This paper develops a two-agent New Keynesian model, which is suitable for identifying the drivers of business cycle fluctuations in small open, resource-rich, resource-dependent emerging economies. We confront the model with Nigerian data on eleven macro-economic variables using the Bayesian likelihood approach and show that output fluctuations are driven mainly by oil and monetary policy shocks in the short run and domestic supply shocks in the medium term. On the other hand, monetary and domestic supply shocks jointly account for around 70 percent of short run variations in headline and core measures of inflation while oil shocks play a less prominent role owing partly to the low pass-through effect arising from the extant fuel subsidy regime in the country. Interrogating these findings further, we find that negative oil price shocks generate a persistent negative impact on output and a short-lived positive effect on headline inflation. In terms of policy responses, the estimated Taylor rule indicates a hawkish monetary policy stance over the sample period while the estimated fiscal rule provides evidence for a pro-cyclical and rather muted fiscal policy. Since domestic supply and oil-related shocks are key sources of macroeconomic fluctuations, the study calls for a more creative use of the country's stabilisation funds as well as strategic fiscal interventions aimed at addressing the issues of domestic supply constraints and promoting private sector investments.
Keywords: E31; E32; E52; E62; 330; Business cycles; resource-rich economy; DSGE model